A transição agroecológica em rizipiscicultura : o caso do assentamento 25 de novembro, Capão do Leão, RS. - Miguens, Fábio Piraine (2007)
Rice-fish growing, based on agroecology, combines the cultivation of irrigated rice and the growing of fish, in the absence of pesticides. Two situations occur: the simultaneous in which rice and fish are grown together and the alternate, which intercalates fish and rice. In a participative work, a reference experiment was installed for the agroecological transition from irrigated rice agroecosystem to produce healthy fish and rice in benefit of agricultural laborers of land reform program. In the years of 2004/2005 a preliminary trial was conducted and in 2005/2006 the research experiment was carried out. An area of 0.5 ha of the Settlement 25 Novembro, in the vicinity of CPATB-Embrapa, Capão do Leão, RS, Brazil, was used. Sixteen (16) experimetal units were built, each with 8.5m x 22.5m (191.25m2 ) consisting of a refuge with 2.5m x 8.5m x 0.7m (14.87m3 ), with controlled irrigation and drainage. A completely randomized experimental design, with 3 replications was used and the following four treatments : T1 (Control) = irrigated rice only (cv. Firmeza); T2 (7020) = irrigated rice + 70% Cyprinus carpio + 20% Ctenopharyngodon idella + 5% Aristichthys nobilis + 5% Hypophthalmichthys molitrix; T3 (4545) = irrigated rice + 45% Cyprinus carpio + 45% Ctenopharyngodon idella + 5% Aristichthys nobilis + 5% Hypophthalmichthys molitrix; T4 (2070) = irrigated rice + 20% Cyprinus carpio + 70% Ctenopharyngodon idella + 5% Aristichthys nobilis + 5% Hypophthalmichthys molitrix. Rice production, fish production, soil fertility and water quality variable data were submitted to analysis of variance (SANEST) and means compared by test of Duncan (P<0.05). Water leaking from tanks through wall of mud, predation of fish by otters (Lutra longicaudis) and maximum rice yields of 5.000 kg. ha -1 were observed. After the conclusion of the experiment a drastic reduction in rice yield was observed, that did not exceed 2.720 kg. ha -1 in T2(7020), probably due to lack of organic fertilization, lack of tillering and etiolation of plants fostered by early watering, absence of water circulation in experimental iunits and by late nitrogen fertilization in all treatments. Water quality parameters were satisfactory for carp growing whereas the best results of weight gain (53.99g) were obtained at 118 days of growing in T3(4545), followed by T4(2070) with 52.77g. At the end of the experiment the hypothesis of this research was not confirmed because the landlles agricultural laborers discontinued the installed production unit system.